TDP-43 and Phosphorylated TDP-43 Levels in Paired Plasma and CSF Samples in Amyotrophic Lateral Sclerosis - Ren, Yuting; Li, Siyuan; Chen, Siyu; Sun, Xiaosun; Yang, Fei; Wang, Hongfen; Li, Mao; Cui, Fang; Huang, Xusheng (Frontiers in Neurology, 2021)
Objective: The aim of this study was to measure both plasma and cerebrospinal fluid (CSF) TAR DNA-binding protein 43 (TDP-43) and phosphorylated TDP-43 (pTDP-43) levels in sporadic amyotrophic lateral sclerosis (sALS) patients, and to compare them with that of healthy controls. The correlation between plasma or CSF TDP-43/pTDP-43 and clinical indicators of ALS patients was assessed. Methods: Paired plasma and CSF TDP-43/pTDP-43 levels in 69 ALS patients and 59 healthy controls were measured by sandwich ELISA. Time to generalization (TTG), an indicator suggested that the time of symptoms spreading from spinal or bulbar localization to both, was evaluated in all patients screened for mutations in genes associated with ALS. Results: Both of the plasma TDP-43 and pTDP-43 levels were significantly higher in ALS patients than HCs (P < 0.001). The pTDP-43/TDP-43 ratios in plasma were significantly higher in HCs than ALS patients (P < 0.001). The area under the curve (AUC) value was 0.924 for plasma TDP-43 level, with a 91.3% sensitivity and 91.5% specificity. Moreover, the correlation between plasma and CSF TDP-43 was observed in each ALS patient (r = 0.195, P = 0.027). A correlation between CSF pTDP-43 levels and the ALSFRS-R (r = −0.245; P = 0.042) was established. A correlation was observed between plasma TDP-43 levels and TTG in ALS patients, which indicated that high levels of plasma TDP-43 correlated with prolonged TTG (r = 0.415; P = 0.004). Conclusion: The plasma TDP-43 and pTDP-43 levels might play an important role in diagnosis in the future study of ALS. The plasma TDP-43 might differentiate ALS and HC groups based on high sensitivity and specificity, and as an indicator of progression of disease.